Developing an Interactive University Orientation App: Potential Users’ Feedback - Ab Rashid, Radzuwan; Annamalai, Nagaletchimee; Saed, Hadeel; Yassin, Baderaddin; Al-Smadi, Omar Ali (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Abstract— The use of apps has become increasingly common in higher institutions and often linked with the needs of the current generation. This qualitative study investigates the perception of undergraduate students at a university in Malaysia as part of a need analysis to develop a university orientation app. Fifteen participants were interviewed and the findings suggest that the participants have a positive perception of having the app. The positive perception is mainly based on the needs to navigate around the campus where the apps will help to make the navigation easier and effective by serving as ‘one-stop information center’. In addition to the navigation purpose, the potential users request gamification elements to keep them interested in using the app. This paper concludes that an appealing orientation app for the students should expose them to the university surrounding and at the same time contain gamification elements.